Design and Implement Deep-Space network and validate its existence against De-authentication attack - Sharma, Kritika (My University, 2019)
Deep Space is full of challenges when it comes to network communication that keeps motivating us to come up with a technology that can withstand constraints and challenges related to this communication. Some of the prominent challenges of Deep Space are intermittent connectivity, huge propagation delays, blackouts, high retransmission rates, high error rates, etc. Consider a scenario in which Google needs to be accessed on Mars. The communication starts by typing in the URL address of Google which afterward is translated to an IP address by DNS. A request for translation is sent to the Earth’s Deep Space Stations (DSS) that is currently in communication with the satellite. In deep space, Round Trip Time (RTT) for communication depends on the current positions of planets for e.g. Earth and Mars communication last somewhere between 7-40 minutes depending on how they are positioned. Even the delays for Geosynchronous satellites last about 250ms. Say it took 14 mins for the request to be handled and in the meantime, the station with which the communication was being held could have moved as planets are constantly in motion i.e. revolving around the sun and rotating about their own axis. This might result in Earthly devices acquiring a different IP address [21]. As a result, communication is not feasible between the two devices. To overcome such challenges researchers came up with Delay and Disruption Tolerant Networking that is independent of end to end path and can handle harsh environments of space. DTN will allow us to test the limits of how far we can go in deep space. Many researchers and various international organizations are working to make it operable to realize its capabilities. But as the technology advances so do the threats associated with it. Space is difficult territory and does not have boundaries as such, which are prevalent in terrestrial networks. If something goes wrong, there isn’t much to rely on. On Earth, even in an event of an attack, it can be resolved with not that much trouble but if this was to happen in Deep Space where the RTT alone takes minutes to hours how can any prolific help be provided in such situation. Security is an important parameter to consider while communicating. As the networks in deep space are wireless, they are prone to a huge number of threats. This research work deals with the query that whether the attacks done on terrestrial networks are also possible in Deep Space as they use the same underlying protocols so they might be prone to the same vulnerabilities. If the attacks are possible how adversely will they affect the productivity of networks? The attack performed for validating the doubts presented is De-authentication attack that disconnects the two DTN nodes communicating to each other in an environment like deep space. This thesis also explores the detection and prevention mechanism for the attacks carried out. The detection mechanism produces an output with the Basic Service Set Identifier (BSSID) of the target and the count of packets addressed to it. There are some mechanisms listed that can be used to protect the devices against the attack performed to make the communication infrastructure secure.
Keywords: Deep Space communication; de-authentication attack; Deep Space network; Contact Window attacks; ION